Alegebraic DOA estimation and tracking using ULV decomposition - Coviello, C; Sibul, L; Yoon, P (2003)
Blind beamforming is an important technique that is used to determine signal sources from the original signals mixed with additive noise and to estimate their direction of arrival (DOA). Before recovering the DOA information, it is necessary to preprocess the data matrix to decorrelate and normalize the mixed sources before applying nonlinear algorithms for the signal separation. A popular choice for the preprocessor has been based on the singular value decomposition (SVD). In this paper we propose an alternative preprocessor based on the ULV decomposition (ULVD). We compare both in an algebraic beamformer in terms of performance and accuracy.